Improving the Competence of Agricultural Machinery Maintenance Training Participants Using the Practical Demonstration Method - Wanda Afnison; Purwantono; Dieter Rahmadiawan; Anna Niska Fauza; Donny Fernandez; Elviza Yeni Putri; Ilham Yuliady (Jurnal Vokasi Mekanika (VoMek), 2026)
This training activity was conducted for a group of farmers in Saureinu Village, Mentawai Islands Regency. Based on the team's observation data, we found that many farmers in Saureinu Village still do not understand how to maintain agricultural machinery. As a result, many agricultural machines in Saureinu Village are damaged and cannot be used, thereby reducing farmer productivity. Through this activity, training on agricultural machinery maintenance was provided to the Saureinu village farmer group using the Practical Demonstration method. The Practical Demonstration method was considered appropriate for participants who had diverse backgrounds and no prior understanding of machinery. Based on the team's assessment at the beginning and end of the activity, there was an increase in the participants' knowledge and competence related to the material provided. In the theory session, participants' knowledge increased by 52%, and in the practice session, participants' competence increased by 40%. Participants' mastery of each sub-topic increased by 35-40%. Based on the conversion of scores to assessment categories, this activity was able to improve participants' competencies from poor to good. This improvement is expected to enable the Saureinu Village farmer group to maintain the agricultural machinery they use and maintain stable agricultural productivity.